Experiences of peer victimization associated with stress and anxiety among adolescents in North Macedonia - Dimitrinka Jordanova Peshevska (University American College Skopje, 2022)
The negative effects of peer victimization are well documented in the research literature showing that bullying victimization is linked to many negative health outcomes, such as: stress, depression, anxiety, and even attempted suicide or committed suicide. The aim of the current study is to investigate the association between peer victimization and mental health (anxiety, stress and depression) in students, based on the ecological framework of understanding violence. The data were collected from a purposive sample that includes 1089 students (57.5per cent female and 42.5per cent male) between the ages of 11 and 18, enrolled in primary and secondary schools in North Macedonia in 2022. All respondents confirmed their and their parent's informed consent to participate. Paper and pen based interviewed questionnaires were used for gathering data from the respondents. The majority of the items were the subscales from the Depression, Anxiety and Stress Questionnaire, Peer Violence Victimization Scale and relevant socio-demographic questions. The study's findings revealed the statistically significant positive correlation between the experiences of peer victimization and both stress and anxiety among students in primary and secondary school settings in North Macedonia. The results show that the regression model statistically significantly predicts 21per cent of the variance of the variable stress (F=63.008, p<.01). Verbal violence, social manipulation and damage to property are statistically positive predictors of stress. The model predicted 16per cent of the variance for the outcome variable of anxiety. The regression model statistically significantly predicts the outcome variable of stress (F=47.432, p<.01). The results reveal that verbal violence, social manipulation and damage to property are statistically positive predictors of anxiety in adolescents. Understanding that experience of peer victimization is a significant risk factor for adolescent's mental health would be an important step in advancing the way we put forward intervention and support programs for adolescent well-being.
Keywords: 330; stress; anxiety; peer victimization; adolescents